Can Islamic Values Support Fraud Prevention in Village Fund Management? A Study in Ngoro Subdistrict, Mojokerto - Albaab, Ahmad Sahilul; Maulah, Lia Hikmatul (ITB AAS INDONESIA Surakarta, 2025)
This study examines the role of Islamic values in preventing fraud in the management of village funds in Mojokerto Regency. Using a quantitative approach, the research involved 57 respondents from Ngoro Subdistrict, directly engaged in village financial management, specifically village heads, secretaries, and treasurers. The findings reveal that Islamic values have a positive and significant effect on fraud prevention efforts, emphasizing their role in enhancing governance integrity. These results highlight the importance of embedding Islamic principles in village governance to enhance transparency and accountability. This study provides recommendations for policymakers and practitioners to integrate Islamic approaches into training programs and village fund management to achieve better governance